Risk Factor Assessment of Lymph Node Metastasis in Patients With FIGO Stage IB1 Cervical Cancer - Xu, Mu; Xie, Xiaoyan; Cai, Liangzhi; Xie, Yongjin; Gao, Qiao; Sun, Pengming (Frontiers in Oncology, 2022)
Objectives To assess the risk factors of lymph node metastasis (LNM) in patients with FIGO stage (2009) IB1 cervical cancer (CC). Methods Patients with FIGO stage IB1 CC who underwent radical resection between 2012 and 2018 were recruited. The risk factors for LNM were analysed. A recursive partitioning analysis (RPA) was used to divide the patients into risk groups and assess their risk of LNM. Results The 5-year overall survival rate was 91.72%, while 80.0% and 93.5% for patients with or without LNM (P<0.05). Multivariable logistic regression analysis showed that lymphovascular invasion (LVI), depth of invasion (DI), tumour size (TS), squamous cell carcinoma (SCC) antigen level were independent risk factors (all P<0.05). Patients were divided into low-risk (no LVI, DI <1/2, TS <2 cm), intermediate-risk (no LVI, DI <1/2, TS ≥2 cm; no LVI, DI ≥1/2, normal SCC level; LVI, DI <1/2, TS <2 cm), and high-risk (no LVI, DI ≥1/2, SCC level ≥1.5 ng/ml; LVI, TS <2 cm, DI ≥1/2; LVI, TS ≥2 cm) groups by RPA according to these four factors. The incidence of LNM among the three groups was 0.00%, 4.40%, and 24.10%, respectively (all P<0.001). The 5-year overall survival rates differed among the groups (98.2%, 92.7%, 83.0%, respectively, P=0.001). Conclusions LNM affects the prognosis of patients with FIGO stage IB1 CC. Lymphadenectomy may be avoided for patients in the low-risk group and recommended for those in the high-risk group. Whether dissection is performed in the intermediate-risk group depends on the lymph node biopsy results.